Ruminative Tendency Relates to Ventral Striatum Functionality: Evidence From Task and Resting-State fMRI - Erdman, Alon; Abend, Rany; Jalon, Itamar; Artzi, Moran; Gazit, Tomer; Avirame, Keren; Ais, Ezequiel Diego; Levokovitz, Hilik; Gilboa-Schechtman, Eva; Hendler, Talma; Harel, Eiran Vadim (Frontiers in Psychiatry, 2020)
Background Ruminative responding involves repetitive and passive thinking about one’s negative affect. This tendency interferes with initiation of goal-directed rewarding strategies, which could alleviate depressive states. Such reward-directed response selection has been shown to be mediated by ventral striatum/nucleus accumbens (VS/NAcc) function. However, to date, no study has examined whether trait rumination relates to VS/NAcc functionality. Here, we tested whether rumination moderates VS/NAcc function both in response to reward and during a ruminative state. Methods Trait rumination was considered dimensionally using Rumination Response Scale (RRS) scores. Our sample (N = 80) consisted of individuals from a community sample and from patients diagnosed with major depressive disorder, providing a broad range of RRS scores. Participants underwent fMRI to assess two modes of VS/NAcc functionality: 1) in response to reward, and 2) during resting-state, as a proxy for ruminative state. We then tested for associations between RRS scores and VS/NAcc functional profiles, statistically controlling for overall depressive symptom severity. Results RRS scores correlated positively with VS/NAcc response to reward. Furthermore, we noted that higher RRS scores were associated with increased ruminative-dependent resting-state functional connectivity of the VS/NAcc with the left orbitofrontal cortex. Conclusions These findings suggest that ruminative tendencies manifest in VS/NAcc reward- and rumination-related functions, providing support for a theoretical-clinical perspective of rumination as a habitual impairment in selection of rewarding, adaptive coping strategies.